Ski jumpers` physical fitness test toolkit for staged progress tests in yearly training cycle: benefits analysis - Lebedev, G. K.; Melnikova, L. V.; Prokopenko, G. Y. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test benefits of a physical fitness progress test toolkit for training stages in an annual training cycle.